2006
DOI: 10.1111/j.1083-6101.2003.tb00215.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Political Conversation on the Internet: Users' Perspectives

Abstract: This essay provides an account of the perspectives of users of online political discussion spaces. In‐depth interviews with 69 people who participate in online political discussion groups were conducted. The interviews suggest that they perceive themselves to be interacting with persons who differ from them. They appreciate and enjoy the diversity of people and opinions they encounter online. Although some interview participants expressed dislike at encountering racist or xenophobic perspectives, others apprec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
0
11

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(119 citation statements)
references
References 8 publications
2
106
0
11
Order By: Relevance
“…Some studies have found participation in online political discussion contributes to political participation (Nah, Veenstra, & Shah, 2006). Others have focused on how agreement and disagreement takes place, and the di erent factors that in uence opinion expression (Kwak, Williams, Wang & Lee, 2005;Wojcieszak & Mutz, 2009), while there is research to suggest online se ings can enrich the diversity of viewpoints (Kelly, Fisher and Smith, 2005;Stromer-Galley, 2003).…”
Section: Discussion Comments On Political User-generated News Websitesmentioning
confidence: 99%
“…Some studies have found participation in online political discussion contributes to political participation (Nah, Veenstra, & Shah, 2006). Others have focused on how agreement and disagreement takes place, and the di erent factors that in uence opinion expression (Kwak, Williams, Wang & Lee, 2005;Wojcieszak & Mutz, 2009), while there is research to suggest online se ings can enrich the diversity of viewpoints (Kelly, Fisher and Smith, 2005;Stromer-Galley, 2003).…”
Section: Discussion Comments On Political User-generated News Websitesmentioning
confidence: 99%
“…Conversely, several other studies of newsgroups and/or news media message boards found that such spaces hosted a diversity of opinions (Graham, 2011;Schneider, 1997;Strandberg, 2008;Tsaliki, 2002). For example, Stromer-Galley's (2003) interviews with participants revealed that people not only meet and engage with different points of view online, but also actively seek it out.…”
Section: Diversity Of Opinionmentioning
confidence: 99%
“…It now covers a variety of research agendas, which include comparisons between face-to-face and online deliberation (Wojcieszak, Baek & Delli Carpini, 2009;Baek, Wojcieszak, & Delli Carpini, 2012); the use of online consultations (Albrecht, 2006;Åström & Grönlund, 2012;Coleman, 2004;Fishkin, 2009;Karlsson, 2012;Kies, 2010;Winkler, 2005); moderation and the design of forums (Bendor, Lyons, & Robinson, 2012;Edwards, 2002;Wright, 2009;Wright & Street, 2007); the extent to which forums facilitate contact between opposing perspectives (Brundidge, 2010;Stromer-Galley, 2003;Wojcieszak & Mutz, 2009); and the effects of online deliberation on civic engagement (Price & Cappella, 2002). One of the most popular lines of research, however, has been the study of informal political talk through the lens of deliberative ideals.…”
Section: Analysing and Assessing Online Political Talkmentioning
confidence: 99%
“…There is considerable discussion about how computer-mediated political discussion might serve as an online "public sphere" in the sense that Habermas [21] described it as an open forum for the rational discussion of diverse views [10,53,54], with considerable attention being paid to whether SNSs narrow or widen political discourse [3,18,28,46,74,[78][79][80][81]87]. More recently, media theorists and sociotechnical researchers have turned their attention to what has been called the "sprawling" public sphere [11] and the hybrid nature of new media [6,29,45,46].…”
Section: Social Media and Civic Participationmentioning
confidence: 99%